Medium-term Philippine development plan, 1999-2004. (Manila, Philippines : National Economic and Development Authority, 1999)
Over the past two planning periods, the Philippines took on the challenge of shaking off its image as southeast asia's basket case. Amidst the difficult task of protecting the democratic gains achieved in 1986, structural reforms were painstaking pursued over the years to gradually free the economy from ineffective government interventions and a system of protection which engendered inefficiency in the production and distribution of goods and services.
Chapter 1. development challenge -- Chapter 2. social reform and development -- Chapter 3. agriculture, agrarian reform and natural resources -- Chapter 4. industry and services -- Chapter 5. infrastructure development -- Chapter 6. governance and institutions development -- Chapter 7. macroeconomics framework and development financing.
Keywords: DEVELOPMENT PLAN